2019
DOI: 10.3389/fbioe.2019.00360
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Antimicrobial Hyaluronic Acid/Quaternized Chitosan Hydrogels for the Promotion of Seawater-Immersion Wound Healing

Abstract: Wound immersion in seawater with high salt, high sodium, and a high abundance of pathogenic bacteria, especially gram-negative bacteria, can cause serious infections and difficulties in wound repair. The present study aimed to prepare a composite hydrogel composed of hyaluronic acid (HA) and quaternized chitosan (QCS) that may promote wound healing of seawater-immersed wounds and prevent bacterial infection. Based on dynamic Schiff base linkage, hydrogel was prepared by mixing oxidized hyaluronic acid (OHA) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 55 publications
2
28
0
1
Order By: Relevance
“…However, it has been proven that for open wounds, local or site-specific sustained release of antiseptics and antibiotics from biomaterials is very effective in reducing systemic side effects related to much higher antibiotic dosages taken orally [127]. The unique chemical interactions of HA with other polysaccharides such as inherently antimicrobial chitosan can be used to produce very effective antiseptic materials such as wound gauzes [128]. Their healing and antiseptic properties can be further boosted by encapsulating proper antiseptics or antibiotics in such HA-chitosan hydrogels.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…However, it has been proven that for open wounds, local or site-specific sustained release of antiseptics and antibiotics from biomaterials is very effective in reducing systemic side effects related to much higher antibiotic dosages taken orally [127]. The unique chemical interactions of HA with other polysaccharides such as inherently antimicrobial chitosan can be used to produce very effective antiseptic materials such as wound gauzes [128]. Their healing and antiseptic properties can be further boosted by encapsulating proper antiseptics or antibiotics in such HA-chitosan hydrogels.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…The in vivo study in a seawater-immersed wound defect model showed that the hydrogels decreased pro-inflammatory factors and promoted anti-inflammatory factors (TGF-β1) in the wound. The hydrogel promoted excellent re-epithelialization, increased the granulation tissue thickness and the density collagen deposition with good antibacterial activity [ 80 ].…”
Section: Preparation Techniques and Properties Of Hydrogelsmentioning
confidence: 99%
“…The new materials are capable of not only preserving the wound environment but also of transferring active compounds to aid in the wound-healing process [14]. In this regard, various wound-dressing products, such as antibacterial creams, ointments, hydrogels, and antibacterial agents in combination with polymers, are currently available and consist mainly of biodegradable materials such as chitosan, hyaluronic acid, collagen, silicon, cellulose, and gelatin [27][28][29][30][31][32].…”
Section: Wound Dressingmentioning
confidence: 99%